Role Paradox of PPKn Teachers in the AI Era: From Instructor to Ethical Guardian - Yasir Marzuqi; Trisna Sukmayadi; Triwahyuningsih Triwahyuningsih; Sunny G. Gabinete; Islahuddin Islahuddin (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
The integration of generative artificial intelligence (AI), particularly ChatGPT and Google Gemini, into Civic and Pancasila Education (Pendidikan Pancasila dan Kewarganegaraan/PPKn) has introduced fundamental shifts in pedagogical practice. While these technologies offer opportunities for more adaptive and personalized learning, they simultaneously risk undermining teachers' epistemic authority and displacing the internalization of Pancasila values that form the ethical core of students' character formation. This study examines the paradox of PPKn teachers' roles amid the proliferation of instant AI tools, analyzes their transition toward ethical guardianship, and proposes pedagogical implications as a pre-policy baseline study. A qualitative approach using Interpretative Phenomenological Analysis (IPA) was employed, involving in-depth interviews with 13 PPKn teachers from the Subject Teacher Forum (MGMP) in Bantul Regency (November 2025–February 2026), supported by classroom observations and document analysis. The findings reveal three interrelated crises: (1) a facilitation paradox, in which the demands of student-centered learning paradoxically compel teachers to adopt defensive strategies including strict digital device monitoring and time-pressured assessments; (2) an epistemic authority crisis, characterized by students' increasing trust in AI-generated responses over teachers' contextual and normative explanations; and (3) the erosion of Pancasila values, encompassing declining empathy and human interaction (Second Principle), weakening deliberative practices (Fourth Principle), and reduced academic integrity (Fifth Principle), as reflected in instant plagiarism and cognitive passivity. In response, this study advances the concept of Guardian Pedagogy as a reconceptualization of the teacher's role in safeguarding students' epistemic, relational, and ethical foundations in the digital age.